Web-Based Employee Performance Assessment Application with SMART Method: An Agile Approach in the Context of the Smartphone Market - Theodore Frederick; Jansen Wiratama; Fransiscus Ati Halim (Universitas Islam Raden Rahmat, Malang, 2024)
Employee performance plays a significant role in determining the company's sustainability, so company leaders must pay attention to employee performance. To determine an employee's performance more objectively, many subjective factors influence it, so performance appraisals only sometimes end up being fair. One of the companies developing in Indonesia is a smartphone sales company, CV Jala Kencana. As the CV Jala Kencana company continues to develop and the number of employees increases, problems arise in assessing employee performance, which still needs to be done objectively. So that employee performance assessments can be more objective, a decision support systems application is needed that can help assess employee performance. The Agile SDLC method is used in designing a website-based employee performance assessment application. Then, for the employee performance assessment feature, the Simple Multi-Attribute Rating Technique (SMART) method is used, and SHA512 encryption is implemented in the Database Management Systems for better database security. This research produces a web-based employee performance assessment application with features for assessing employee performance based on predetermined criteria.